The Influence of Work Culture, Creativity and Innovation toward Competitive Advantage on Small Batik Industry in Pamekasan - Firmansyah, Farid (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2019)
Small batik industry in Pamekasan spread across several districts, with the biggest distribution was spread in Proppo District and the smallest was in Waru district. The Numbers of batik Craftsmen declined in some districts, the largest declining happened in Galis district. The phenomenon of competition on small batik industry in Pamekasan attracted researcher using variables of Work Culture, Creativity, Innovation and Competitive Advantage. The sample of this study was seventy-five SMEs. The conclusions of this research were: 1. Partially, three independent variables used in this study influenced. 2. Creativity has a positive and significant impact. 3. The effect of product innovation on competitive advantage can be feasible models